Implementation Of A Web-Based Chatbot Using Machine Learning For Question And Answer Services In Universities - Dewantara, Airlangga Satria; Aryanto, Joko (Advance Sustainable Science, Engineering and Technology, 2024)
Advances in communication technology in line with information technology, Chatbot is an innovation that combines communication technology and information technology, is an application that can communicate with humans like a virtual assistant who can respond and answer every question asked. A university must already have a website that can be accessed by the general public so that information about the college can be accessed by everyone anywhere and anytime. To make it easier to get information on the website, chatbots can be the solution because most prospective students and students who are on the campus feel reluctant to browse further into the website that has been provided and usually only open the main homepage page of the website. Parents of students also find it difficult to find out what is on campus if a lot of information is provided in certain tabs of the website. In this study, I utilized Chatbot technology which is a Machine Learning that can process every text that inputted then analyze it and conduct machine training using the Neural Network algorithms that have been provided. This research uses a case study methodology, with Yogyakarta University of Technology as the subject, to develop a chatbot website that incorporates machine learning to facilitate the processing of user input questions